Elevated anal squamous cell carcinoma risk associated with benign inflammatory anal lesions. Issue 5 (18th November 2005) - Nordenvall, C; Nyrén, O; Ye, W
Abstract : Background: The association between benign anal lesions and anal cancer is still unclear. Few data from large cohort studies are available. Methods: We conducted a register based retrospective cohort study including 45 186 patients hospitalised for inflammatory anal lesions (anal fissures, fistulas, and perianal abscesses) as well as 79 808 haemorrhoid patients, from 1965 to 2002. Multiple record linkages identified all incident anal (squamous cell carcinoma only) and colorectal cancers through to 2002. Relative risk was estimated by standardised incidence ratio (SIR), the ratio of observed number of cases divided by that expected in the age, sex, and calendar year-matched general Swedish population. Results: There was a distinct incidence peak in the first three years of follow up among patients with inflammatory lesions. SIR then levelled off at around 3 and remained at this level throughout follow up (SIR during years 3–37 of follow up was 3.3 (95% confidence interval 1.8–5.7)). A similar initial incidence peak was observed among haemorrhoid patients but was confined to the first year; SIR was 2.8 in the second year, and then it decreased further and was close to unity in the following years (SIR during years 3–37 was 1.3 (95% confidence interval 0.7–2.1)). Among inflammatory lesion and haemorrhoid patients, a significantly increased risk of colorectal cancer was observed only in the first year after hospitalisation. Conclusions: Inflammatory benign anal lesions are associated with a significantly increased long term risk of anal cancer. In contrast, haemorrhoids appear not to be a risk factor for this malignancy.